Ragam Storyboard Untuk Produksi Media Pembelajaran - Imbar Nursetyo, Kunto; Ariani, Diana; widyaningrum, retno; syahyani, regita (Universitas Negeri Jakarta, 2021)
The media producer must be able to design the message and then simultaneously visualize the idea of the message before continuing it at the next production stage of various media formats that may be developed for learning. As for seeing the needs of the Education Technology study program students related to the production of learning media, the researcher determined the purpose of this study was to produce a variety of storyboards for the production of instructional media. The ADDIE development framework is used in this development research, while the procedures in this model are carried out linearly or a work process will occur continuously. The following are the steps that will be carried out in this research: Analysis (Analyze.), Design (Design), Development (Implementation), Implementation (Implementation), Evaluation (Evaluation). The output in the form of a storyboard for digital media production is the result of this development, which consists of two storyboard template formats based on linear and non-linear presentation flows. Mahasiswa sebagai media developer harus mampu mendesain pesan kemudian secara simultan melakukan visualisasi ide dari pesan tersebut sebelum melanjutkannya pada tahap produksi selanjutnya dari beragam format media yang mungkin dikembangkan untuk pembelajaran. Adapun melihat kebutuhan dari para mahasiswa terkait produksi media-media pembelajaran, maka dengan ini peneliti menentukan tujuan dari penelitian ini adalah menghasilkan ragam storyboard untuk produksi media pembelajaran. Model pengembangan yang digunakan pada penelitian pengembangan ini adalah dengan menggunakan framework ADDIE, adapun pada ADDIE ini dilakukan secara linear atau akan terjadi proses kerja yang dilakukan secara kontinyu prosesnya. Berikut langkah-langkah yang akan dilakukan dalam penelitian ini: Analisis (Analyze.), Desain (Design), Pengembangan (Development), Implementasi (Implementation), Evaluasi (Evaluation). Hasil dari penelitian pengembangan ini adalah produk berupa storyboard untuk produksi media digital berdasarkan alur penyajian yang terdiri dari dua format template storyboard linear dan non-linear.